Long-Term Crustal Deformation along the Southern Java Subduction Margin Revealed by GNSS Observations - Friska, Vira; Marzuki, Marzuki; Nurdin, Nurdin; Monica, Fadilla (Jurnal Ilmu Fisika, 2026)
This study examines long-term GNSS-derived velocities along southern Java during 2011–2020 to characterize regional crustal deformation. Data from six InaCORS stations operated by BIG were processed using GAMIT/GLOBK to produce time series and estimate horizontal and vertical velocities. Horizontal velocities range from 21.35 mm/yr to 27.54 mm/yr toward the southeast, reflecting strong Eurasian Plate influence. The time series indicates gradual, continuous displacement without significant co-seismic offsets, despite several Mw ~6 earthquakes in the region. Vertical velocities show both uplift and subsidence, ranging from −13.84 mm/yr to 12.61 mm/yr, likely resulting from combined tectonic and non-tectonic processes. Because vertical GNSS measurements generally have higher uncertainty, these results must be interpreted cautiously. Although station motions appear stable, this does not indicate low seismic hazard. Instead, it may suggest ongoing strain accumulation within a seismic gap that could generate a future major earthquake. Overall, these findings enhance understanding of southern Java’s subduction dynamics and support improved earthquake hazard assessment and disaster preparedness.